Research on Initial Teacher Education in Germany – A Survey of recent Empirical Studies - Schaefers, Christine (Swiss Journal of Educational Research, 2002)
Against the background of the current discussion about teacher education in Germany, this article gives a survey of the recent findings of German research on initial teacher education (first and second phase of the German teacher education system). The few, mostly quantitative, cross-sectional studies, predominantly give only selective insights into the complex system of teacher education. It is a systematic, theory-based teacher education research that is particularly lacking, as well as wide-ranged evaluation studies which would allow drawing comparisons among teacher education models of the different locations and regions in Germany. Only if teacher education research offers solid empirical knowledge about the system and its effectiveness can sound decisions about the further development, restructuring, or revision of teacher education be possible.